Comparação do sucesso na produção e qualidade de embriões entre um laboratório convencional e um laboratório ISO 5/7 e fatores relacionados a gravidez - Gontijo, Érica Eugênio Lourenço (2016)
INTRODUCTION: The frequency of embryo production and successful pregnancy are the main parameters used to measure the quality of human reproduction laboratories. OBJECTIVE: We compared the success in the production and quality of embryos, success rate and factors related to pregnancy in LabRep/HC/UFG before deep adjustments estrututurais, when it was classified as conventional laboratory and after adequaçãos, when it began to be classified as an ISO 5/7 laboratory and factors related to the success of fertilization. METHOD: The study was divided into two parts. The first evaluated the embryo quality and the second risk factors capable of interfering with the success of pregnancy. information of 278 cycles of women were surveyed who submitted any Assisted Human Reproduction technique during the study period. In the first analysis were surveyed: cleavage of the embryo, the result of βHCG, embryo quality and microbiological contamination of the means of embryos crops. In the second, they evaluated the size of follicles per woman, amount of aspirated oocytes, raised, inseminated and injected, ovarian stimulation scheme, maternal infections, infertility period and sperm quality. The study design was a case control. Data were entered into Epi-Info 3.3.2 and analyzed in BioEstat 5.3 program. We evaluated the relationship between the groups and the factors and the success of pregnancy the odds ratio (OR) and chi-square test (p = 0.05). RESULTS: In the first analysis it was observed that the ISO 5/7 laboratory, there were successful in the formation of embryos and the conventional O , CI - 2: 0.24, p: 0.81). 5/7 96.6% ISO laboratory embryos were generated A or B, since the conventional laboratory, 90.4% were A or B. The pregnancy success in the laboratory I O was , and conventional laboratory O CI to 2: 2,24; p: 0.13). The second correlation was found with pregnancy failure female factors: having more than 40 years (OR 6.04, CI: 1.34 to 27.08; p: 0.010), higher infertility time 97 months (OR: 4.49, CI: 1.65 to 12, .21; p: 0.00) and have endometrial thickness of less than 10mm (OR: 5.42, CI: 2.44 to 12.05; p:0.001). The male factors with correlation were: oligozoospermia (OR:3,35; IC:1,41-7,92; p:0,010) e teratozoospermia (OR:4,14; IC:1,89-9,07; p:0,010).Microbiological contamination was found in 11.06% of semen samples. CONCLUSIONS: There was no statistical difference between the results of the two laboratories, however we observed a trend of better quality embryos in ISO 5/7 laboratory. It was concluded that the patients attended the LabRep/HC/UFG, present a great heterogeneity of clinical profiles and different reproductive characteristics. It shows how a major challenge that encourages the ongoing investment in cutting edge technology and processes, as well as constant improvement of the multidisciplinary team that make up the lab.